Investment in Human and Nonhuman Capital, Transfers Among Siblings, and the Role of Government - Nerlove, Marc; Razin, Assaf; Sadka, Efraim (Econometrica, 1984)
[The implications for efficient allocation of parents' inability to force transfers among siblings are explored. When there are differences in abilities of children within families, such transfers may be necessary to achieve a first-best solution. In the absence of such transfers, a tax on earned income and a subsidy to inheritance are useful second-best tools, whereas subsidies to investments in human capital or physical capital are not desirable.]